Primary Central Nervous System Sarcoma in Pediatrics: Clinical characteristics and outcomes at a national referral center in Peru - Raymundo-Ricalde, Sergio (2024)
Introduction: Primary central nervous system (CNS) sarcomas are one of the rarest tumors in pediatrics, and an increase in the frequency of these cases has been observed in Peru. This article describes the clinical, demographic characteristics, and survival of pediatric patients with this condition diagnosed at the National Institute of Neoplastic Diseases (INEN). Methods: This is a descriptive observational case series study of a retrospective longitudinal design. Data was collected from 51 patients aged 0-18 years diagnosed with malignant CNS sarcoma between 2009 and 2019 at INEN, and statistical analysis was conducted using the STATA software program. Results: The male-to-female ratio was 1.23. The most common birthplace was Lima. The average age was 7.6 years, and the most frequent location was supratentorial (96.08%; 49/51). There was only one patient with leptomeningeal metastasis. The most common clinical features were nausea, vomiting, and headache, and the most used postoperative therapeutic regimen was ICE-RT local-ICE. The 5-year overall survival (OS) was 47.06%, and the event-free survival (EFS) was 35.19%. Conclusions: The survival rate of patients with primary CNS sarcoma in pediatrics is low compared to other pathologies; a study of factors that may influence the results of this group of patients is required.